Mowgli's story - Ovitz, Mark H.; Marck, Nick (USA : Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
This story, is a hilarious fun-filled, live-action adventure complete with the beloved characters from Rudyard Kipling's timeless tale
Editor, Alan Baumgarten ; executive producer, Barry Bernard
Keywords: Animal films; Animals in motion pictures; Wildlife films